Alloactivation of Naïve CD4+CD8−CD25+T Regulatory Cells: Expression of CD8α Identifies Potent Suppressor Cells That Can Promote Transplant Tolerance Induction - Verma, Nirupama D.; Robinson, Catherine M.; Carter, Nicole; Wilcox, Paul; Tran, Giang T.; Wang, Chaunmin; Sharland, Alexandra; Nomura, Masaru; Plain, Karren M.; Bishop, G. Alexander; Hodgkinson, Suzanne J.; Hall, Bruce M. (Frontiers in Immunology, 2019)
Therapy with alloantigen-specific CD4+CD25+ T regulatory cells (Treg) for induction of transplant tolerance is desirable, as naïve thymic Treg (tTreg) are not alloantigen-specific and are weak suppressor cells. Naïve tTreg from DA rats cultured with fully allogeneic PVG stimulator cells in the presence of rIL-2 express IFN-gamma receptor (IFNGR) and IL-12 receptor beta2 (IL-12Rβ2) and are more potent alloantigen-specific regulators that we call Ts1 cells. This study examined additional markers that could identify the activated alloantigen-specific Treg as a subpopulation within the CD4+CD25+Foxp3+Treg. After culture of naïve DA CD4+CD8−CD25+T cells with rIL-2 and PVG alloantigen, or rIL-2 without alloantigen, CD8α was expressed on 10–20% and CD8β on <5% of these cells. These cells expressed ifngr and Il12rb2. CD8α+ cells had increased Ifngr that characterizes Ts1 cells as well was Irf4, a transcription factor induced by TCR activation. Proliferation induced by re-culture with rIL-12 and alloantigen was greater with CD4+CD8α+CD25+Treg consistent with the CD8α+ cells expressing IL-12R. In MLC, the CD8α+ fraction suppressed responses against allogeneic stimulators more than the mixed Ts1 population, whereas the CD4+CD8−CD25+T cells were less potent. In an adoptive transfer assay, rIL-2 and alloantigen activated Treg suppress rejection at a ratio of 1:10 with naïve effector cells, whereas alloantigen and rIL-2 activated tTreg depleted of the CD8α+ cells were much less effective. This study demonstrated that expression of CD8α by rIL-2 and alloantigen activation of CD4+CD8−CD25+Foxp3+T cells was a marker of activated and potent Treg that included alloantigen-specific Treg.